Melamine-Formaldehyde Polymer-Based Nanocomposite for Sunlight-Driven Photodegradation of Multiple Dyes and Their Mixture - Garg, Anjali Kumari (Langmuir : the ACS journal of surfaces and colloids, 2023)
Cadmium sulfide (CdS)-decorated, cross-linked melamine-formaldehyde polymer-based nanocomposite (MFP-CdS) has been synthesized. MFP-CdS is utilized here as a photoactive material for the photodegradation of six model organic dyes and their mixture in an aqueous medium in the presence of sunlight. The half-life values from the kinetic study of multiple dyes strongly support the importance of sunlight on the fast degradation of all six dyes compared to bulb light and control (dark) conditions. A comparative 1H NMR analysis of the dyes and their degraded products has been performed to support the breakdown of the aromatic framework of organic dyes using MFP-CdS in sunlight. The mechanisms involved in the photodegradation of dyes have been investigated based on radical trapping studies that support the significant involvement of superoxide radicals along with holes. Moreover, the dye removal efficiency using MFP-CdS from real industrial wastewater samples is evaluated via the external spiking of organic dyes and their mixture in unknown industrial effluents where they showed similar photodegradation results. Based on the high recyclability of MFP-CdS, these are used for multiple cycles